2021
DOI: 10.3390/ma14020443
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability of Poly (N-Isopropylacrylamide) Anchored on the Surface of Gold Nanoparticles

Abstract: To verify the temperature sensitive failure of poly (N-isopropylacrylamide) (PNIPAM) anchored on the surface of gold nanoparticles (AuNPs), the UV-Vis spectra with temperature variations of the following aqueous solutions respectively containing AuNPs-PNIPAM, Au-PNIPAM/PNIPAM, PNIPAM, in different media (including salt, ethanol, HCl and cetyltrimethylammoniumbromide (CTAB)), were systematically determined. The results indicated that the UV-Vis spectrum of AuNPs-PNIPAM suspension hardly changed even above the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The disadvantage of the catalyst being ineffective at higher temperatures was observed in the case of rigid core@polymeric shell HMGs, which was quite similar to the homogenous HMGs. Han et al [32], Minier et al [49], and Li et al [26] observed a similar trend of the reduction in the catalytic efficacy of HMGs owing to steric hindrance. The synthesis mechanism associated with the fabrication of the rigid core@polymeric shell is presented in Figure 11.…”
Section: Heterogeneous Hmgsmentioning
confidence: 68%
See 1 more Smart Citation
“…The disadvantage of the catalyst being ineffective at higher temperatures was observed in the case of rigid core@polymeric shell HMGs, which was quite similar to the homogenous HMGs. Han et al [32], Minier et al [49], and Li et al [26] observed a similar trend of the reduction in the catalytic efficacy of HMGs owing to steric hindrance. The synthesis mechanism associated with the fabrication of the rigid core@polymeric shell is presented in Figure 11.…”
Section: Heterogeneous Hmgsmentioning
confidence: 68%
“…For instance, the polymerization techniques of reversible-addition chain-fragmentation transfer (RAFT) [24] and selective bond formation techniques [25] have been used alongside FEPol for the development of HMGs. Li et al [26] synthesized Au NPs using citrate reduction methodology and anchored two successive shells of PNIPAM layers (via FEPol) over these NPs by carrying out a polymerization reaction containing the dispersion of Au NPs in the reaction pot.…”
Section: In Situ Generation Of Nms Within Microgelsmentioning
confidence: 99%
“…We hypothesized that the interactions between AuNPs and proteins can perturb the local environment of AuNP‐dye complexes, causing conformational changes in AuNPs and hence changing the signals of dyes. To support our hypothesis, we chose COOH−Py and incubated methanol with the complex, providing a model for dye release by protein binding [53,54] . Methanol can interact with AuNPs via hydrophobic interactions and hydrogen bonds, similar to proteins [55] .…”
Section: Resultsmentioning
confidence: 99%
“…To support our hypothesis, we chose COOHÀ Py and incubated methanol with the complex, providing a model for dye release by protein binding. [53,54] Methanol can interact with AuNPs via hydrophobic interactions and hydrogen bonds, similar to proteins. [55] Ultraviolet-visible spectroscopy (UV-Vis) is an effective method to detect effects of such environmental changes on AuNPs.…”
Section: Development and Characterization Of Sensor Arraysmentioning
confidence: 99%
“…For such a purpose, an interesting type of polymer is the temperature-sensitive poly( N -isopropylacrylamide), or PNIPAAM, because its structural features can be tuned by temperature [ 9 ]. It is well-known that high-molecular-weight PNIPAAM dissolved in water undergoes coil-to-globule transition when the temperature exceeds its lower critical solution temperature, LCST ≈ 32 °C [ 10 ].…”
Section: Introductionmentioning
confidence: 99%